The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1063/1.350646
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of Pd/Ni alloys for detection of high hydrogen concentrations

Abstract: Thin alloy films of Pd and Ni (8%<Ni<20% in at. %) formed by dual-electron-beam evaporation techniques have been found to give durable and quickly reversible detectors of high H2 concentrations (pH2 0.1%–100%, 0.7–700 Torr) near 1 atm and 300 K, including accurate determinations of pH2 around the lower explosive limit of 4% in air. The addition of Ni suppresses the α to β phase transition found in pure Pd under these conditions. The measurement of resistivity changes in the thin films along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(127 citation statements)
references
References 9 publications
4
118
0
Order By: Relevance
“…In conclusion, it was found that an alloy of composition Pd77-Ag 23 at wt% can be deposited by co-sputtering from separate pure metal targets, which is a powerful method that can be used to fabricate many other types of alloy films with highly accurate compositional control, see also [20].…”
Section: B Deposition Of Pd-ag Alloy Film By DC Co-sputteringmentioning
confidence: 99%
“…In conclusion, it was found that an alloy of composition Pd77-Ag 23 at wt% can be deposited by co-sputtering from separate pure metal targets, which is a powerful method that can be used to fabricate many other types of alloy films with highly accurate compositional control, see also [20].…”
Section: B Deposition Of Pd-ag Alloy Film By DC Co-sputteringmentioning
confidence: 99%
“…In addition, the phase transition from α phase of Pd to the "hydride" β phase occurs at fairly low hydrogen partial pressures, and this transition leads to irreversible structural changes in Pd [6,7]. To improve these drawbacks, films of Pd-based alloys, such as Pd-Mg [8], Pd-Au [9], Pd-Ag [10], and Pd-Ni [11][12][13] alloys, have been investigated. Among these candidates, the Pd-Ni alloy has been spotlighted due to its durability and fast response.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the gas sensors available on the market are inorganic metal oxide semiconductor-based sensors which can be operated at high temperature to ensure the sensitivity and selectivity of the sensors [5][6][7]. However, new sensing materials are expected to have a high gas-sensing ability at room temperature [8].…”
Section: Introductionmentioning
confidence: 99%